Leitura à primeira vista: perspectivas para a formação do violonista - Arôxa, Ricardo Alexandre de Melo (2013)
The current job Market demands, increasingly, instrumentalists with skills and theoretical and practical knowledge in various styles and musical genres. This situation brings up new questions and concerns in music scientific research. From the dialogue between the subareas of Musical Education and Performance, emerges the subarea of Pedagogy of Musical Instrument that investigates tools and pedagogical practices inherent to the instrumentalists teaching and learning process. Its purpose is to make this context even more reflective and skillful in adapting to the different styles in which the instrument can communicate its musical art. In case of formal education in classical guitar instrument the can appropriate and transmit music in its various ways the practice of sight-reading becomes an issue facing the needs of this instrument that is essentially soloist. However, the increased participation of the guitar in chamber music groups has set the sight-reading as an important tool for the preparation of the performance. This work shows the importance of sight-reading in the classical guitarists formation process and aims to present, analyze and reflect on issues about teaching and learning of sight-reading in the classical guitarists formation process. The research methodology is based on a qualitative approach and uses bibliographic and documental research, semi-structured interviews with expert classical guitarists at the sight-reading such as Eduardo Fernández, Eduardo Meirinhos, Fábio Zanon, Mario Ulloa and Nícolas de Souza Barros. The theoretical background about Musical Cognition, Musical Education and Performance dialogues with the empirical background of the investigated expert guitarists. As a result of the research, we conclude that the classical guitar learning finds itself undergoing a conceptual and methodological transition process, but it can be improved by using several practices which can be embedded on guitarists routine in order to provide a more accurate and deliberate development of the sight-reading.